PRESENTATION PATTERN AND FUNGAL AGENTS SPECTRUM CAUSING OTOMYCOSIS - DEKHIL, KASSIM R. (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was aimed to identify the pattern of presentation, influencing factors, and sort of the fungal species, distribution of sex of patients with otomycosis. Methods: Eighty-six patients attended to Ad-Diwaniyah teaching hospital, Iraq were screened for identification of fungi causing otomycosis from October 2014 to November 2015. 50 patients were females while 36 patients were males. 12 patients of the total number were with bilateral involvement. Diabetes mellitus, leukemia, chemotherapy, and chemoradiation were the associated systemic diseases which were recorded in patients with otomycosis and diabetes mellitus was detected in 53.84% of patients with systemic diseases. Results: The predominant complaints were pruritus and found in 76 patients (88.73%), discomfort and pain found in 62 patients (72.09%), aural fullness in 48 patients (55.81%), tinnitus in 34 patients (39.53%), hearing impairment in 50 cases (58.31%), ear discharge in 22 patients (25.58%), and most of the symptoms seen in 36 patients (68.14%). The results showed a total of eight fungal species belong to six different genera, namely, Aspergillus, Candida, Penicillium, Rhizopus, Alternaria, and Cephalosporium were isolated during this study. Among identified fungi, Aspergillus niger was found to be the most prevalent fungal species with 35.71% followed by Candida albicans (27.55%), Aspergillus flavus (10.20%), Aspergillus fumigatus (8.16), Penicillium digitatum (6.12%) and Cephalosporium species (4.08%), and Rhizopus species (5.1%), while Alternaria alternata had the lowest percentage (6.54%). Conclusion: Otomycosis/mycotic otitis externa is still a common problem and there is a rise in the occurrence of otomycosis in latest years, especially in tropical and subtropical humid climates.